EVALUATION OF THE IMPLEMENTATION OF THE PRACTICAL EXAM OF THE MUHARRIKUNAJAAH ISLAMIC EDUCATION CENTER - Abdul Rahman Mujahid (Makkah: Journal Of Islamic Studies, 2025)
Practical examinations are essential components of the Islamic boarding school system as they assess students cognitive, psychomotor, and affective competencies in an integrated manner. This study aims to describe the implementation of practical exams at Pusat Pendidikan Islam Muharrikunajah (PPIMN) and identify the supporting and inhibiting factors. A descriptive qualitative method was used involving four examiners responsible for tahfidz, Arabic, fiqh, and English subjects. Data were collected through semi-structured interviews and documentation of assessment rubrics, then analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the practical exams were generally conducted effectively, yet several obstacles occurred such as insufficient early socialization, sudden policy changes, low motivation among final-year students, and the absence of standardized assessment rubrics across subjects. These findings highlight the need for strengthened planning, standardized instruments, and improved coordination among stakeholders. The study recommends developing an official guideline for practical examinations and providing examiner training to enhance objectivity and consistency of assessment.